The Effect of White Lead Tree (Leucaena leucocephala) Leaves Compost and Biocon-NP to the Growth of Long Bean Plants (Vigna sinensis L.) in Lapindo Mud Media - Sabrina, Jhulia Ayu; Rahayu, Yuni Sri; Rahajeng, Saptini Mukti (LenteraBio : Berkala Ilmiah Biologi, 2025)
Lapindo mud, which is abundantly available, requires improvement by adding organic materials and microbes to be used as planting media. The purpose of this study is to describe the impact of Leucaena leaves compost and Biocon-NP on the growth of long beans in Lapindo mud media. This experimental study employed a Randomised Group Design testing, two factors were tested that was Leucaena leaves compost (0 grams, 50 grams, and 100 grams) and Biocon-NP (0 ml, 125 ml, and 150 ml) with three replications. Vegetative parameters were identified, including plant height, number of leaves, root length, wet biomass, root nodule biomass, and active root nodule biomass. The observed generative parameters were age at first flower appearance, number of flowers, pods, and pod biomass. Two-way ANOVA was used to analyse the data, and then Duncan’s test was performed. The outcome of the study indicated that the combination of 100 grams of Leucaena leaves compost and 150 ml Biocon- NP significantly increased plant height, wet biomass, root nodule biomass, active root nodule biomass, flowerage, number of flowers, number of pods, and pod biomass. Overall, our results demonstrate that the application of 150 ml of Biocon-NP in conjunction with 100 grams of Leucaena leaves compost increases the height of the plant, wet biomass, root nodule biomass, active root nodule biomass, age at first flower appearance, number of flowers, number of pods and pod biomass.